The Role of the Language Layer in Customer Communications Management (CCM) - Renuka Kulkarni (North American Journal of Engineering Research, 2023)
In the world of globalized business that we live in today, companies get in touch with clients in different parts of the world, different cultures, and languages as they operate throughout the globe. The point of effective communication is customer satisfaction, trust building, and fulfilling all the regulatory requirements. Customer Communications Management (CCM) systems have become integral in managing communications with customers. It is responsible for the timely delivery of personalized and legal correspondence to the customers. To create personalized communications for the customers residing in different parts of country/globe and communicating in various languages the language layer is one of the most important elements of the CCM systems. It is used in the case of enterprises that want to deliver the same message in more than one other language. The core part of the system is the language layer which will help the companies to have multilingual communications so that both culturally and linguistically, the messages will be accurate. This paper provides an insightful perspective of how the language layer in CCM systems directly impacts multilingual support, content localization, dynamic content generation, personalized messaging, regulatory compliance, and the overall customer's experience.